The maize ID1 flowering time regulator is a zinc finger protein with novel DNA binding properties - Kozaki, Akiko (Oxford University Press, 2004)
The INDETERMINATE protein, ID1, plays a key role in regulating the transition to flowering in maize. ID1 is the founding member of a plant-specific zinc finger protein family that is defined by a highly conserved amino sequence called the ID domain. The ID domain includes a cluster of three different types of zinc fingers separated from a fourth C2H2 finger by a long spacer; ID1 is distinct from other ID domain proteins by having a much longer spacer. In vitro DNA selection and amplification binding assays and DNA binding experiments showed that ID1 binds selectively to an 11 bp consensus motif via the ID domain. Unexpectedly, site-directed mutagenesis of the ID1 protein showed that zinc fingers located at each end of the ID domain are not required for binding to the consensus motif despite the fact that one of these zinc fingers is a canonical C2H2 DNA binding domain. In addition, an ID1 in vitro deletion mutant that lacks the extra spacer between zinc fingers binds the same 11 bp motif as normal ID1, suggesting that all ID domain-containing proteins recognize the same DNA target sequence. Our results demonstrate that maize ID1 and ID domain proteins have novel zinc finger configurations with unique DNA binding properties.